An investigation into conceptual metaphors denoting time in truyện kiều versus romeo and juliet by william shakespeare - Nguyễn,Thị Ngọc Hiền (2016)
This study aims at conducting a contrastive analysis of conceptual metaphor denoting time in Truyện Kiều by Nguyễn Du and Romeo and Juliet by Shakespeare on the background knowledge of cognitive semantics raised by Lakoff and Johnson in their book Metaphors We Live By (1980) and by Kövecses in his book Metaphor (2010). Among four types of conceptual metaphors, the research paper just concentrates on the structural metaphors expressing time. The descriptive and contrastive methods are used in combination with the qualitative and quantitative approaches in order to help the researcher achieve the aims and objectives proposed. The data for analysis were taken from the two masterpieces with 272 samples of conceptual metaphors of time in total (143 samples in Truyện Kiều and 129 samples in Romeo and Juliet). At the result, we have figured out 17 conceptual metaphors of time in Truyện Kiều and 15 conceptual metaphors of time in Romeo and Juliet. The study has pointed out the similarities as well as the differences of conceptual metaphors denoting time in both works. Besides giving an in-depth understanding of conceptual metaphors of time in both works, the research is carried out with the hope of adding the voice to the variety of conceptual metaphors. Moreover, making a contribution to the variety of conceptual metaphors is also our desire. In addition, implications of the thesis could be a useful reference for those who are interested in teaching and learning conceptual metaphors.